Systemic Approach to the Development of Independent English Study Skills in Upper-Secondary School - Deimante-Hartmane, Dagnija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article focuses on the issue of the development of students’independent study skills within the school environment linking the study process with activities carried out after classes. Systemic approach to studies implemented both by teachers and students ensures logical and natural connection with students’ study activities after school. Systemic approach to studies creates school environment that promotes willingness to succeed and school environment that supports learning leads to systemic approach to studies after classes. Research shows that both students and teachers understand the importance of the development of independent study skills.